Comparison of the properties and mechanisms of action of poly-L-lactic acid and polydesoxyribonucleotide (Research, Society and Development, 2025)
This article aims to compare the properties and mechanisms of action of poly-L-lactic acid and polydeoxyribonucleotide through a non-systematic narrative review of the literature. Poly-L-lactic acid (PLLA) and polydeoxyribonucleotide (PDRN) are biomaterials used in minimally invasive cosmetic procedures to correct and control fine wrinkles, moisture, porosity, and oiliness of the dermis and epidermis. They are also used as accelerating agents in wound and scar repair. However, their properties and mechanisms of action are not fully understood and are often confused by clinicians. This article explores the mechanisms of action and main properties of PLLA and PDRN as pharmacological agents. It addresses their definitions, properties, known mechanisms of action, and clinical applications. Understanding the interaction between these agents offers a new perspective on the treatment of various conditions, from wounds and scars to skin rejuvenation.